Pemberdayaan UMKM melalui Pengembangan Jaringan Pemasaran Berbasis Digital di Kabupaten Bolaang Mongondow Selatan - Sudarsono; Djamila Podungge; Aryati Hamzah; Amnatia Abdullah (Journal of Hulonthalo Service Society (JHSS), 2023)
The aim of implementing this community service activity is to grow and develop the ability of MSME actors to become strong and independent in order to increase the role of MSMEs in regional development, job creation, income distribution, economic growth and poverty alleviation in South Bolaang Mongondow Regency. The method of implementing community service is carried out through a series of activity stages as follows: 1) socialization of program plans and service activities to partners; 2) preparing programs and plans for service activities for partners; 3) implementation of training and mentoring; and 4) evaluate each series of service activities for partners. The results of the implementation show an increase in the quality of life of actors and the active participation of partners in implementing science and technology in the fields of production, management and marketing. The process of implementing community service focuses on training and mentoring MSMEs in managing and storing raw materials based on a Point of Sales (POS) System; production; operational management, work standards and SOPs; financial and accounting management through the MYOB Accounting application; labeling and packaging; building marketing networks; creating commerce and Marketplace social media accounts; creating cloud computing-based marketing content; and digital content distribution.